Mengasihi Saudara-Saudara Seiman Berdasarkan Surat 1 Yohanes 3:14 dan Hambatan Dalam Penerapannya - Oilla, Mordikai Mantur; Sugiharto, Ayub (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2023)
Humans as social creatures are supposed to live side by side with each other, but the reality that occurs in the history of human life is that conflicts often occur between fellow humans, whether in the family environment, social life or in the world of education and in the work environment; The point is that wherever there is social interaction, there is potential for conflict between humans. This problem occurred not by coincidence but as a result of the sinful human nature inherited from generation to generation from the first humans (Adam and Eve) but also as a way of life for humans in general at the end of time which is always selfish. With the presence of various modern technologies that attract attention and make it easier to meet everyone's needs, the circulation of hoax news and hate speech has also caused a lot of social conflict and caused a lot of commotion. Here is the presence and testimony of Christians as children of God who have received the gift of salvation; who have passed from death into life and enjoy fellowship with God who is Love, are required to show a different way of life, namely practicing a life of mutual love in social interactions with fellow humans in general, especially in fellowship with fellow believers or brothers. members of faith in a community or in a local church. Based on this reality, this research will discuss how love for fellow believers is proof of salvation so that every believer can live a life of love for one another.